UNGGULAN DAYA SAING ARSITEK PROFESIONAL DALAM PERSAINGAN GLOBAL - ISMADI B. Siswanto (Jurnal Teknik Sipil dan Arsitektur, 2008)
Service construction world claimed to be able to share in the form of effort handling of process of design and built professionally. One of the conducting able to be used in supporting profession in design and built construction service area is principals applying of scheme and execution of development in unity of process develop; build In free trade era, hence activity of building engineering need the readiness of from since feasibility study, scheme, levying of goods, construction, conservancy and operation, and environment in it environmental and finical environment.As characterization of key in construction service se, Architect is one of the past master giving contribution determine in area of design and built, and expected can professionally share at building engineering and scheme. Ability of this professional is one of the important condition to can to compete freely in globalization era. Knowledge Architect which professionally can involve and pour the him of by organized in unity of development process which is systematic to be, expected can become capital in following free computation, specially at scheme process and building engineering. Research to 41 professional Architect in Yogyakarta, Surakarta and Semarang, conductedr with method analyse to relation between Architect knowledge to scheme process and building engineering which related to construction service industries, passing coefficient test ofconcordancy, and correlation test. Result of discussion show indication still got by him some weakness which often happened in course of designing to wake up, in the form of lack of Architect knowledge, either from education background side, job experience, strive development of knowledge, work type variation, and role of in profession and organization, capable to by totally and organized use development process through principals applying of building engineering and scheme.Through this research, is expected by the condition can anticipate, specially will the growing of emulation with foreign construction service, with past master owning storey level domination of information, technological, and capital owning big potency to conduct emulation.Â